Perbandingan Respons Penyembuhan Jaringan Periodontal pada Anak Stunting dan Status Gizi Normal Berdasarkan Profil Interleukin-6 - Meiza Nerawati; Nila Kasuma; Fathurrahman Ariza Busril (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Introduction: Stunting has long-term effects on child growth and development and may be associated with oral health and immune responses. Gingivitis is an inflammatory periodontal condition characterized by the activation of various inflammatory mediators, including interleukin-6 (IL-6). This study was conducted among children aged 6–12 years in the working area of Lubuk Kilangan Community Health Center, Padang City, Indonesia.Objective: To compare the periodontal healing response following scaling and root planing (SRP) between children with stunting and those with normal nutritional status based on clinical parameters and salivary IL-6 levels.Methods:This experimental study employed a pretest–posttest group design involving 60 children aged 6–12 years with gingivitis who were selected using simple random sampling, comprising 30 children with stunting and 30 children with normal nutritional status. Clinical parameters included the Oral Hygiene Index (OHI) and Gingival Index (GI), while the molecular parameter was salivary IL-6 level. All parameters were assessed before SRP and four weeks after SRP.Results: Significant improvements in clinical periodontal parameters were observed after SRP in both groups. Salivary IL-6 levels also decreased significantly in the stunting and normal nutritional status groups, with mean reductions of 2.37 pg/mL (p<0.001) and 3.36 pg/mL (p=0.002), respectively.Conclusion: SRP resulted in improvements in clinical periodontal parameters and reductions in salivary IL-6 levels in both children with stunting and those with normal nutritional status. However, the clinical improvement in the stunting group was less pronounced than in the normal nutritional status group. These findings suggest that periodontal healing responses may be influenced by both local and systemic factors. Periodontal management in children with stunting should consider systemic conditions, including nutritional status and oral health education.